Trends in Cardiovascular Disease Risk and Outcomes Among Asian Communities Post-COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Lisy Augustin; Thephilah Cathrine R (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Abstract Background: The COVID-19 pandemic has significantly impacted cardiovascular health, particularly in Asian populations. These communities already experience high rates of cardiovascular diseases (CVD), exacerbated by various socio-economic, lifestyle, and genetic factors.  This systematic review and meta-analysis aimed to evaluate the impact of the COVID-19 pandemic on cardiovascular disease risks and outcomes in Asian populations. Methods: Studies published between 2020 and 2025 were included, focusing on adults (≥18 years) from Asian countries. A random-effects model was employed to pool effect sizes, and heterogeneity was assessed using the I² statistic. Risk of bias was evaluated using the Newcastle-Ottawa Scale. Subgroup analyses were conducted based on geographic region, pre-existing comorbidities, and study design. Results: The pooled odds ratio (OR) for increased cardiovascular risk post-COVID-19 was 3.59 (95% CI: 3.58–3.61), indicating a significant rise in risk. Individuals with pre-existing comorbidities, especially DM and HTN, faced a higher risk of severe outcomes. DM alone increased mortality risk by 69%, and when combined with cardiovascular disease, the risk was even higher (OR = 6.98).